1994
DOI: 10.1002/ijc.2910570511
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mapping of chromosome 19 in human gliomas

Abstract: There is evidence that a putative glioma tumor suppressor locus resides on the long arm of chromosome 19. We present data on 161 gliomas from 156 patients, which were studied by microsatellite analysis for loss of heterozygosity (LOH) on chromosome 19. Eight loci on the long arm and 2 loci on the short arm of chromosome 19 were examined. LOH on 19q was observed in 3/19 astrocytomas (WHO grade II), 12/27 anaplastic astrocytomas (WHO grade III), 16/76 cases of glioblastoma multiforme WHO (grade IV), 4/9 oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…Multiple investigations have progressively narrowed the 19q common deletion region to an interval within the 19q13.3 cytogenetic band (120,(122)(123)(124), and several positional and/or functional candidates for the 19q tumor suppressor gene have been eliminated based on mutational analyses (125)(126)(127)(128)(129)(130). The 19q glioma tumor suppressor gene, however, remains to be identified.…”
Section: Chromosome Arm 19qmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple investigations have progressively narrowed the 19q common deletion region to an interval within the 19q13.3 cytogenetic band (120,(122)(123)(124), and several positional and/or functional candidates for the 19q tumor suppressor gene have been eliminated based on mutational analyses (125)(126)(127)(128)(129)(130). The 19q glioma tumor suppressor gene, however, remains to be identified.…”
Section: Chromosome Arm 19qmentioning
confidence: 99%
“…Deletion mapping of 19q in oligodendrogliomas is complicated by the rare occurrence of tumors with only partial deletion of 19q. Thus, hypothesizing that astrocytic and oligodendroglial tumors share at least one 19q tumor suppressor gene in common, deletion mapping studies of the oligodendroglioma 19q gene have primarily relied upon astrocytoma samples (120,(122)(123)(124).…”
Section: Chromosome Arm 1p and 19qmentioning
confidence: 99%
“…Comprehensive genomic characterization by integrative analysis of DNA copy number, gene expression and DNA methylation aberrations in >200 glioblastomas has then refined the definition of human glioblastoma genes and core pathways (The Cancer Genome Atlas [TGCA] Research Network, 2008). Deletion of chromosome 19q is nevertheless of particular interest, as it is shared by all three glioma subtypes, occurring in approximately 75% of oligodendrogliomas, 45% of mixed oligoastrocytomas and 40% of astrocytomas (von Deimling et al, 1992(von Deimling et al, , 1994, where it is associated with the transition from low-grade to anaplastic tumours (Ohgaki et al, 1995;Ritland et al, 1995;Smith et al, 1999) (Box 2).…”
Section: Non-random Chromosomal Aberrations In Gliomas: the 19q13 Abnmentioning
confidence: 99%
“…Further studies have shown that oligodendroglial tumors display a distinctive genetic pro le that consists of loss of the entire 1p and 19q chromosomal arms with retention of 1q and 19p (Kraus et al, 1995;Ritland et al, 1995). Although the smallest region of overlapping deletion on 19q has been narrowed to a 900-kb region (Rosenberg et al, 1996;Yong et al, 1995), the small deletions have generally been in astrocytic lesions, not oligodendroglial ones (Ritland et al, 1995;von Deimling et al, 1994). The incidence of 19q loss for oligodendroglial tumors is as high as 81% in some studies (Reifenberger et al, 1994), while LOH for 1p has been reported in up to 94% of these tumors (Bello et al, 1995).…”
Section: Reports By Ransom Et Al (1991) and Von Deimling Et Al (199mentioning
confidence: 99%